The Role of Adenosine Receptors and AMPK in Mouse FDB Muscles During Fatigue - McRae, Callum (Université d'Ottawa / University of Ottawa, 2023)
Muscle fatigue is an intrinsic myoprotective process that prevents damaging ATP depletion during intense or prolonged exercise by limiting ATP demand when ATP production becomes insufficient. One mechanism of fatigue involves a reduction in membrane excitability with the opening of ATP-sensitive K+ (KATP) and ClC-1 Cl- channels, resulting in submaximal sarcoplasmic reticulum Ca2+ release and reduced force generation, but the intracellular signalling pathways for this process is unknown. As a first step toward understanding this process, the objective of this study was to test the hypothesis that adenosine receptors (ARs) and AMPK trigger fatigue when a metabolic stress occurs during muscular activity. Compared to control conditions, a pan-activation of ARs with 10 µM adenosine and NECA initially reduced the fatigue rate during the first 60 s of a 3 min fatigue bout triggered with 1 tetanic contraction every s. An activation of the A1 adenosine receptor (A1R) with 10 and 20 µM ENBA resulted in faster rate of fatigue; an effect blocked by 5 µM DPCPX, an A1R antagonist. At 10 and 20 µM, adenosine, NECA, and ENBA activated AMPK via an increased in T172 phosphorylation. At 10 µM, MK8722, an AMPK agonist, initially caused a reduction in fatigue rate during the first 60 s followed by an increased fatigue rate during the last 2 min of the fatigue bout. Co-activation of ARs and AMPK did not give rise to either an additive or synergistic effect. FDB from AMPK α1-/- and α2-/- mice had faster fatigue rate and greater increased in unstimulated force compared to FDB from AMPK α1+/+ and α2+/+ mice. It is suggested that ARs and AMPK play a role in the mechanism of fatigue when a metabolic stress develops during muscle activity.
Keywords: Skeletal Muscle; Muscle Fatigue; Membrane Excitability; Flexor Digitorum Brevis; Adenosine; AMPK